2016
DOI: 10.17261/pressacademia.2016219945
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of User Insights for E-Health Development Challenges in Turkey, Kingdom of Saudi Arabia, Egypt and United Arab Emirates

Abstract: Implementation of e-health is expected to affect the outcomes of medical services positively, by contributing to the effectiveness and efficiency of overall healthcare ecosystem. This becomes more crucial in developing countries where access, finance, resources and competent professionals in healthcare are limited. This field study assesses healthcare professionals' insights, for the major challenges of ehealth development with a distinctive model and comparative analysis in four emerging countries; Turkey, Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…It was indicated that some countries, including Saudi Arabia, face many challenges with using telehealth in general, such as a general distrust of electronic business, privacy concerns, cultural factors, adoption by users, and technological infrastructure. [ 30 ] Also, a recent systematic review concluded that the e-health system in Saudi Arabia is growing thanks to the efforts of Vision 2030 and the goals planned for the year 2020, but the review also stated that these goals were not completely fulfilled. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that some countries, including Saudi Arabia, face many challenges with using telehealth in general, such as a general distrust of electronic business, privacy concerns, cultural factors, adoption by users, and technological infrastructure. [ 30 ] Also, a recent systematic review concluded that the e-health system in Saudi Arabia is growing thanks to the efforts of Vision 2030 and the goals planned for the year 2020, but the review also stated that these goals were not completely fulfilled. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…10 Similarly, e-health improves diagnosis and treatment, reduces waiting times, and facilitates diseases prevention and care coordination. 11 Though e-health has good prospects for providing improved health services and quality to people at a lower cost, its adoption and acceptance processes are not equally straightforward; in reality, understanding the acceptance or rejection of new information systems is regarded as a challenge in the field of information systems. 12 Regarding Saudi Arabia, it is a diverse and fast progressing country and its GDP was 0.3% in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis of four developing countries namely Turkey, Saudi Arabia, Egypt, and United Arab Emirates was conducted by Uluc & Ferman (2016) to determine the challenges faced by healthcare professionals in using e-health technology. The study identified ICT infrastrucuture, policy regulations, clinical adaptation of users, healthcare financing, and supply chain management as the major challenges faced by the healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%